Anti-Virulence Activity of the Cell-Free Supernatant of the Antarctic Bacterium Psychrobacter sp. TAE2020 against Pseudomonas aeruginosa Clinical Isolates from Cystic Fibrosis Patients - Rosanna Papa; Gianluca Vrenna; Caterina D’Angelo; Angela Casillo; Michela Relucenti; Orlando Donfrancesco; Maria Michela Corsaro; Ersilia Vita Fiscarelli; Vanessa Tuccio Guarna Assanti; Maria Luisa Tutino; Ermenegilda Parrilli; Marco Artini; et al. (Antibiotics, 2021)
Pseudomonas aeruginosa is an opportunistic pathogen often involved in airway infections of cystic fibrosis (CF) patients. Its pathogenicity is related to several virulence factors, such as biofilm formation, motility and production of toxins and proteases. The expression of these virulence factors is controlled by quorum sensing (QS). Thus, QS inhibition is considered a novel strategy for the development of antipathogenic compounds acting on specific bacterial virulence programs without affecting bacterial vitality. In this context, cold-adapted marine bacteria living in polar regions represent an untapped reservoir of biodiversity endowed with an interesting chemical repertoire. In this paper, we investigated the biological activity of a supernatant derived from a novel Antarctic bacterium (SN_TAE2020) against specific virulence factors produced by P. aeruginosa strains isolated from FC patients. Our results clearly show a reduction in pyocyanin and protease production in the presence of SN_TAE2020. Finally, SN_TAE2020 was also able to strongly affect swarming and swimming motility for almost all tested strains. Furthermore, the effect of SN_TAE2020 was investigated on biofilm growth and texture, captured by SEM analysis. In consideration of the novel results obtained on clinical strains, polar bacteria might represent potential candidates for the discovery of new compounds limiting P. aeruginosa virulence in CF patients.